Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41467-020-20646-7
|View full text |Cite
|
Sign up to set email alerts
|

A structural polymer for highly efficient all-day passive radiative cooling

Abstract: All-day passive radiative cooling has recently attracted tremendous interest by reflecting sunlight and radiating heat to the ultracold outer space. While some progress has been made, it still remains big challenge in fabricating highly efficient and low-cost radiative coolers for all-day and all-climates. Herein, we report a hierarchically structured polymethyl methacrylate (PMMA) film with a micropore array combined with random nanopores for highly efficient day- and nighttime passive radiative cooling. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
321
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(359 citation statements)
references
References 55 publications
6
321
0
Order By: Relevance
“…41 Similarly, by coupling the effect of microspheres and microstructure surfaces (Figure 8D), polymer coatings with a porous surface can potentially be used for PDRC application; these coatings can be easily painted by the volatilization of the solvent, 15 or the dissolution of the sphere template. 67,68 A high value of ε LWIR = 0.97 at 25 C has been achieved in both experiments and simulations. 15,56 However, the volatile solvent used in the preparation of porous coatings increases the content of volatile organic compounds (VOCs).…”
Section: Improved Thermal Mid-infrared Emittancementioning
confidence: 78%
See 1 more Smart Citation
“…41 Similarly, by coupling the effect of microspheres and microstructure surfaces (Figure 8D), polymer coatings with a porous surface can potentially be used for PDRC application; these coatings can be easily painted by the volatilization of the solvent, 15 or the dissolution of the sphere template. 67,68 A high value of ε LWIR = 0.97 at 25 C has been achieved in both experiments and simulations. 15,56 However, the volatile solvent used in the preparation of porous coatings increases the content of volatile organic compounds (VOCs).…”
Section: Improved Thermal Mid-infrared Emittancementioning
confidence: 78%
“…Source: Reproduced with permission: Copyright 2021, Spring Nature. 67 (I) Textile reflector based on the polymer (such as: PEO). Source: Reproduced with permission: Copyright 2021, Spring Nature 76…”
Section: Colored Pdrc Coatingmentioning
confidence: 99%
“…When the thickness increases to the millimeter level, the transmittance almost decreases to zero and thus the emissivity reaches the maximum. [7,39] In this study, the nano-micro-structured plastic is different from the previously reported textiles or polymer films with the relatively thin thickness at the micrometer level; it is prepared with the thickness at the millimeter level. Therefore, the nano-micro-structured plastic's emissivity and radiative cooling efficiency are almost irrelevant to the millimeter-level thickness.…”
Section: Photonic Properties Of the Nano-micro-structured Plasticmentioning
confidence: 98%
“…[ 5,6 ] Currently, porous polymer structures without doped scattering particles are rising to replace such conventional nanoparticle composites. [ 7–9 ] Nevertheless, it is a grand challenge to make porous polymer structures with significant scattering ability due to the intrinsic low refractive index of polymers. In recent years, Cyphochilus scale made of biopolymer chitin has become an inspiration source for making highly scattering porous polymer films due to its excellent scattering performance stemming from refined porous network.…”
Section: Introductionmentioning
confidence: 99%